Intentions, attitude beliefs, social norm beliefs, and past behavior relationships based upon perceived environmental and health factors for participants involved in outdoor land-based trail recreation in Wisconsin - Melby, J. D. (My University, 1994)
Ajzen and Fishbeins' Theory of Reasoned Action was used to measure the attitude beliefs, social norm beliefs, and intentions in predicting the correlates of participation in ~utdoorla nd-based trail recreati~nb ased upon perceived environmental and health factors. Additionally, Ajzen and Fishbeins' behavioral model was modified to include self-report past behavior as suggested by Manfredo and Shelby (1987). A sample of 75 members of the Wisconsin Wildlife Federation were questioned regarding their intentions to participate in nonmotorized trail recreation, their attitude beliefs regarding participation, the influence of important others in making decisions to participate, and their past behavior in either motorized or nonmotorized land-based trail recreation. It was found that the attitude and social norms accurately predicted intentions to participate in nonmotorized recreation (R = .91). Standardized regression coefficients demonstrated that intentions were influenced more by attitudes (r = .92, p < .01) than by the influence of social references (r = .59, p < .01). The past behavior variable also indicated significant correlation to the attitude (r = .29, p < .05) and social norm (r = .26, p < .05) components within a modified model. This supports findings by Manfredo and Shelby (1 987) on the validity of self-reported past behavior in studies of attitude-behavior relationships. Although significant differences using the intention and past behavior variables were found, further investigations using a larger sample size are needed. This study suggests that there are both natural environment and health needs factors which participants in outdoor trail use consider when determining motorized versus nonmotorized uses of land-based trail recreational sites.
Keywords: Outdoor recreation - Psychological aspects; Environmental psychology; Trails - Environmental aspects - Wisconsin; Recreational surveys - Wisconsin